State Power and Record-Keeping: the History of Individualized Surveillance in the United States, 1790-1935 - Sankar, Pamela L (1992)
This dissertation charts the emergence of individualized record-keeping in the United States by tracing the history of criminal identification records and the invention of statistically-based identification systems, which the state applied to the population in general. The dissertation ties the invention of these individualized record-keeping systems to the development of a state surveillance capacity and its need for fixed, official identities. The dissertation situates this investigation in the history of writing and argues that to understand the roots of writing's power in contemporary society, essentialist assertions about writing's utility and superiority must be replaced with investigations of how writing was transformed into a critical source of state power. Of particular interest here is how the construction of centralized, state-administered records extended and elevated the state's organizational memory. The dissertation starts with a detailed examination of the earliest US reform prison where the link between individual identities and state surveillance was first forged. It continues with an analysis of the emergence of state identification practices from local into national arenas that focuses on the appearance of practices associated with preventive policing in the mid-1800s. The dissertation then describes the invention and application of statistically-based identification methods, including criminal anthropometry and fingerprinting. These statistical methods could be applied reliably to large populations and thus allowed the state to expand its identification interests beyond criminals to the population at large. The dissertation closes with a description of the construction of the US national fingerprint system. In describing each of these phases, the dissertation analyzes both the motives which inspired proponents of improved identification systems and the actions they took to invent, refine, and deploy new methods to serve those motives. This analysis locates the power of writing in complex record-keeping practices, usually invisible because so commonplace, and re-casts state record-keeping systems from by-products of pragmatic bureaucratic activity into intentionally created, carefully fostered reservoirs of state power